Clinical Outcomes Of Descemet Membrane Endothelial Keratoplasty Using The Bonfadini-Todd Injector For Graft Insertion - Ighani, Mehrnaz (Clin Ophthalmol, 2019)
PURPOSE: To evaluate the clinical outcomes of using an Alcon intraocular lens (IOL) B cartridge for graft insertion during Descemet membrane endothelial keratoplasty (DMEK). PATIENTS AND METHODS: We retrospectively reviewed medical charts of patients who underwent DMEK using the Bonfadini-Todd injector, composed of an Alcon IOL B cartridge connected to plastic tubing and a syringe, for graft insertion between May 2016 and August 2018. Patient demographics, diagnoses, donor information, visual acuity, intraocular pressure (IOP), graft position and attachment status, pachymetry, and postoperative complications were recorded. RESULTS: Twenty-four eyes of 23 patients with an average age of 72.8 ± 10.0 years (range, 48–87 years) were included. Mean follow-up duration was 13.3 ± 6.6 months (range, 3–26 months). Twenty-one (87.5%) patients had a primary diagnosis of Fuchs endothelial dystrophy, two (8.3%) patients had bullous keratopathy and one (4.2%) had Peter’s anomaly. Sixteen (66.7%) cases combined phacoemulsification and IOL implantation. Best-corrected visual acuity improved from a median of 0.398 logMAR preoperatively to 0.097 logMAR (P <0.001) at last follow-up examination, and central corneal thickness decreased from a median of 651 μm to 533.5 μm (P <0.001). Nine of 24 patients (37.5%) required re-bubbling due to partial graft detachment with a mean time of 12.1 ± 9.2 days (range, 5–35 days). One patient (4.2%) developed graft failure after re-bubbling and underwent Descemet stripping endothelial keratoplasty. CONCLUSION: The Alcon IOL B cartridge for DMEK graft insertion is safe and simple.